Ionic Liquids for Chloromethane/Isobutane Distillative Separation: Express Screening - Mokrushin, Vladimir; Mokrushina, Liudmila; Arlt, Wolfgang; Assenbaum, Daniel; Wasserscheid, Peter; Petri, Martin; Wewers, Wolfgang (Chemical Engineering & Technology, 2010)
The present study centres on room-temperature ionic liquids (ILs) as entrainers in extractive distillation of chloromethane/isobutane mixtures. The binary system, chloromethane/isobutene, is an azeotropic system. In this study, IL entrainers are shown to be able to break the azeotrope and, thus, assure the separation in the whole range of chloromethane/isobutane ratios. ILs formed from different cations and anions are considered and their influence on chloromethane/isobutane separation is explored. Among the ILs studied, those containing the trifluoromethanesulfonate ([CF(3)SO(3)](-)) or tricyanomethanide ([C(CN)(3)](-)) anion are demonstrated to exhibit an enhanced potential for chloromethane/isobutane separation compared to the corresponding ILs based on the bis(trifluoromethylsulfonyl)imide ([Tf(2)N](-)) anion. Moreover, the ILs enclosing these anions are cheaper than those with the [Tf(2)N](-) anion. Thus, the separation ability, solubility of chloromethane/isobutane mixtures, and costs of IL entrainers can be adjusted by the right choice of cations and anions.
Keywords: Chloromethane-isobutane mixture; COSMO-RS; Express screening experiments; Extractive distillation; Headspace chromatography; Ionic liquids